PERAN QUALITY OF HUMAN RESOURCES DALAM MENINGKATKAN KINERJA PEGAWAI MELALUI SELF ESTEEM SEBAGAI VARIABEL INTERVENING - Nurul Hikmah, Siti Ulya; Sutianingsih, Sutianingsih (Universitas Boyolali, 2023)
This research examines how human resource quality and self-esteem influence employee performance at Notary/PPAT Made Linggarasih, SH. The questionnaire method was used to collect responses to this quantitative research. The sample for this study consisted of 30 people who participated in the survey. Path analysis and linear regression analysis are two data analysis approaches used in this research. The first thing this analysis shows is that the quality of a person's human resources can have a major impact on the level of self-esteem that person has. As a result, the level of performance achieved by employees is greatly influenced by factors such as the quality of human resources and the extent to which individuals believe in their own worth. Based on the results of the Sobel test, a person's sense of self-esteem can act as a moderator between the quality of human resources and the performance of a Notary/PPAT employee Made Linggarasih, SH.